2016
DOI: 10.1063/1.4940949
|View full text |Cite
|
Sign up to set email alerts
|

A physical model for the reverse leakage current in (In,Ga)N/GaN light-emitting diodes based on nanowires

Abstract: We investigated the origin of the high reverse leakage current in light emitting diodes (LEDs) based on (In,Ga)N/GaN nanowire (NW) ensembles grown by molecular beam epitaxy on Si substrates. To this end, capacitance deep level transient spectroscopy (DLTS) and temperature-dependent current-voltage (I-V) measurements were performed on a fully processed NW-LED. The DLTS measurements reveal the presence of two distinct electron traps with high concentrations in the depletion region of the p-i-n junction. These ba… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 58 publications
(86 reference statements)
4
39
1
2
Order By: Relevance
“…where Ea is the activation energy, k is Boltzmann's constant, and T is the stage temperature. This type of carrier transportation, as noted in a previous study, is similar to the classical Poole-Frenkel effect, in which an external field is applied to lower a Coulombic well formed by the deep center and in which the carrier can either be thermally activated and emitted or tunneled through this lowered barrier [21,22]. Fig.…”
Section: Diode I-v Under Different Temperaturesupporting
confidence: 75%
See 3 more Smart Citations
“…where Ea is the activation energy, k is Boltzmann's constant, and T is the stage temperature. This type of carrier transportation, as noted in a previous study, is similar to the classical Poole-Frenkel effect, in which an external field is applied to lower a Coulombic well formed by the deep center and in which the carrier can either be thermally activated and emitted or tunneled through this lowered barrier [21,22]. Fig.…”
Section: Diode I-v Under Different Temperaturesupporting
confidence: 75%
“…In our devices, we found that leakage current could change markedly with temperature (−55°C to 300°C). Specifically, in the low temperature regime, the VRH current changed slowly with temperature variation, whereas in the high temperature regime (where our measurements were conducted), the current increased rapidly, according to this Arrhenius relation [21,22]…”
Section: Diode I-v Under Different Temperaturementioning
confidence: 84%
See 2 more Smart Citations
“…Генерация электронов и дырок происходит в области пространственного заряда (ОПЗ) p−n-перехода, где существует достаточно сильное электрическое поле, которое оказывает влияние на величину тока. В большинстве работ, которые исследуют обратные вольт-амперные характеристики полупроводниковых приборов, это явление остается без внимания, а в других влияние приложенного напряжения объясняется эффектом Пула-Френкеля [15,16]. Коэффициент Пула-Френкеля имеет четко определенное теоретическое значение.…”
Section: Introductionunclassified